Hermeneutik post-strukturalis atas Yohanes 4:1-26 - John Simon; Henderikus Nayuf; Resty T. Arnawa (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
This paper studies John 4: 1-26 in a post-structuralist hermeneutical perspective. Hermeneutics is the art of understanding, namely understanding a text, aiming to reveal the meaning contained in the text. In this case, what is meant is a post-structuralist hermeneutics which assumes that the meaning of a text lies not behind the text but in front of it. With this assumption, the meaning is beyond the author's interests, thus opening up the possibility for the polysemy of meaning found by the reader today. Four successive contextual concerns that can be examined hermeneutically in the narrative of John 4:1-26 are the context of injustice, poverty, radicalism, and ecological damage. These four context challenges are also the challenges facing the churches in Indonesia, which they grapple with in the 16th Session of the Communion of Churches in Indonesia (CCI) in Nias and the 17th in Sumba. The results of the hermeneutics study arrived at the praxis of the holistic liberation of Jesus to overcome these four challenges. They can be used as a praxis for the holistic ministry of the churches today.Â AbstrakTulisan ini adalah sebuah kajian atas Yohanes 4:1-26 dengan perspektif hermeneutik post-strukturalis. Hermeneutik adalah sebuah seni memahami, yaitu memahami teks, yang tujuannya untuk mengungkap makna yang terdapat di dalam teks. Hermeneutik yang dimaksud adalah hermeneutik post-strukturalis yang basisnya bahwa makna teks tidak terletak di belakang teks melainkan di depannya. Karena makna ada di depan teks, maka makna melampaui kepentingan pengarang, yang berarti membuka kemungkinan bagi polisemi makna yang ditemukan oleh pembaca masa kini. Secara berturut-turut empat keprihatinan kontekstual yang dapat ditelaah secara hermeneutis ke atas narasi Yohanes 4:1-26 adalah konteks ketidakadilan, kemiskinan, radikalisme dan kerusakan ekologi. Keempat tantangan konteks ini juga menjadi tantangan gereja-gereja di Indonesia seperti yang digumuli dalam Sidang Raya Persekutuan Gereja-gereja di Indonesia (PGI) XVI di Nias dan XVII di Sumba. Hasil kajian secara hermeneutis menibakan pada praksis pembebasan Yesus yang holistik, untuk mengatasi keempat tantangan konteks tersebut dan dapat dijadikan praksis pelayanan holistik gereja-gereja di hari ini.